Representation of character education values in the tradition of "sikarume" Toraja - Trika Sudarsi, Elim; Taula’bi’, Nilma; Girik Allo, Markus Deli (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
Sikarume tradition (playing puzzles) is almost invisible in family activities or in leisure by the Toraja community. In fact, sikarume contains educational value in general and is even very influential in the development of character education of the Toraja community. The objective of this study is to investigate the values of educational character in the tradition of Sikarume Toraja. This study uses qualitative method; in collecting data from participants, research develop a from of protocol for recording data. In selecting research subjects, researchers applied purposive sampling techniques. The subjects of this study are speakers of Sikarume toraja activities, toraja people, and experts in Toraja language and culture. Data is collected and analyzed in the form of observations and interviews. The data analysis technique in this study is a cyclical model. This study showed that that representations of character education in the tradition of  Sikarume Toraja in this study are peace love in karume allina kukalessekko' and dikeke' napakekke', social care on karume to siruran dao langi' tangsipeta'daan uainna, toena' kunukkun, and toena' kualangko, honest on karume indo' lai' diong to tallang metamba-tamba laboko, hard work on karume mengkalaokan kemakale' ta'pa dio randan langi', responsibility on karume tomenteka torro tanga, creative on karume banuanna nene'ki saratu pentiroanna, and religious there is karume tomate disa'pa-sa'pa.